Tumor Extraction and Volume Estimation for T1-Weighted Magnetic Resonance Brain Images (Global Journal of Computer Science and Technology, 2012)
Magnetic resonance imaging (MRI) is a significant imaging technology for brain tumor diagnosis because physicians can identify precise pathologies by studying the variations of tissue characteristics that occurs in various kinds of MR images. Segmentation of MRI is a pre-process in determining the volume of different brain tissues, but here tumor detection is of primary concern. We proposed a method to extract tumors as seen through MR brain images using co-clustering and morphological operations and its volume estimation was done by Cavalier2019;s estimator of morphometric volume method. Quantitative analysis showed that the proposed method yielded better results in comparison with fuzzy c-means algorithm (FCM)
Keywords: tumor extraction; co -clustering; morphological operations; skull removal; magnetic resonance imaging; volume estimation